Developing a Python-Based Application for a Discrete-Time Population Dynamics Model - Nadhilah, Farhah; Panigoro, Hasan S.; Arsal, Armayani; Nurwan, Nurwan; Wungguli, Djihad; Hasan, Isran K. (Indonesian Journal of Computational and Applied Mathematics, 2025)
Difference equation is a type of equation in mathematics that is widely used to describe certain phenomena as time changes, one of which is in the field of population dynamics. In various studies, it is explained that solving complex population dynamics models is by using numerical simulations. Along with the development of technology, computational science is used to help solve mathematical problems that are difficult to solve analytically. One of them is to use a programming language, such as Python, to help present data in a graphical form. This research aims to develop an application that presents a computational solution to a difference equation using Python. The numerical results begin by entering the equation and variable values into the application, which then automatically generates a figure according to the entered equation. The figures generated in the application include one-dimensional and two-dimensional time series, as well as a Bifurcation diagram.